2007
DOI: 10.1016/j.jmps.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Shock enhancement of cellular structures under impact loading: Part I Experiments

Abstract: This paper aims at showing experimental proof of the existence of a shock front in cellular structures under impact loading, especially at low critical impact velocities around 50 m/s. First, an original testing procedure using a large diameter Nylon Hopkinson bar is introduced. With this large diameter soft Hopkinson bar, tests under two different configurations (pressure bar behind/ahead of the supposed shock front) at the same impact speed are used to obtain the force/time histories behind and ahead of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(97 citation statements)
references
References 25 publications
2
94
1
Order By: Relevance
“…The specific difficulty of using DIC for elastomeric materials is the large amplitude of displacements that may prevent a proper determination of the displacement [38][39][40]. To overcome this difficulty, images were acquired at small loading increment (typically for an incremental axial strain of order 2-3 %) and the displacement analysis was partitioned into subseries (the displacement field was computed from time t i to time t j , for t j − t i < 50 images).…”
Section: Dic Principlementioning
confidence: 99%
“…The specific difficulty of using DIC for elastomeric materials is the large amplitude of displacements that may prevent a proper determination of the displacement [38][39][40]. To overcome this difficulty, images were acquired at small loading increment (typically for an incremental axial strain of order 2-3 %) and the displacement analysis was partitioned into subseries (the displacement field was computed from time t i to time t j , for t j − t i < 50 images).…”
Section: Dic Principlementioning
confidence: 99%
“…They noted that strain rate effects were higher for a higher density and attribute this to the kinetics of internal gas flow. Elnasri et al [9] reported a limited rate sensitivity for ALPORAS foam at strain rates up to 1300 m/s. Zhao and Abdennadher [10] stated that the rate sensitivity of metallic foam is due to inertia effects in dynamic buckling of cell walls, although the foam is made of strain rate insensitive material.…”
Section: Introductionmentioning
confidence: 99%
“…Significant enhancement of crushing stress was observed in the dynamic impact experiments of woods (Reid and Peng, 1997;Harrigan et al, 2005), aluminum honeycombs (Zhao and Gary, 1998;Hou et al, 2012) and foams (Mukai et al, 1999;Deshpand and Fleck, 2000;Tan et al, 2005a;Elnasri et al, 2007). Several shock models and mass-spring models have been proposed to understand the shock wave propagation in cellular materials under dynamic impact, such as the R-PP-L (rate-independent, rigid-perfectly plastic-locking) model (Reid and Peng, 1997), the mass-spring model (Li and Meng, 2002), the E-PP-R (elastic-perfectly plastic-rigid) model (Lopatnikov et al, 2003), the power law densification model and the D-R-PH (dynamic, rigidplastic hardening) shock model .…”
Section: Introductionmentioning
confidence: 97%